The spatial effect of airport proximity on house prices: a quantile regression analysis for the New Zealand market - Squires G; Ngo T; McCord MJ; Lo D; Wang X (Taylor and Francis Group, 2025)
This study contributes to understanding the link between the housing market and airport location proximity, whilst examining the entirety of the house price distribution. The research investigates this association across four key urban areas within New Zealand proximal to an international airport–Auckland, Wellington, Christchurch, and Queenstown. Applying hedonic and quantile regression, the analysis reveals that proximity to airports on house prices has a heterogeneous pricing effect. Results show that distance comprises a positive pricing effect within Auckland and Christchurch, whereas in Wellington and Queenstown the pricing effect is negative. The quantile regression findings further revealed differences between lower and higher priced properties value, given distance and proximity to airports within each city region. The Christchurch region reveals contrasting findings, showing there to be a higher positive pricing effect for higher-priced housing, which gradually decreases when moving down the quantiles. It is argued that this higher positive pricing for higher priced properties is due to particularities in the housing market close to Christchurch Airport.
Keywords: Air-traffic activity; cities; amenities; hedonic pricemodel (HPM); heterogeneity